Identifikasi Kawasan Rawan Bencana Banjir di Sepanjang Aliran Sungai Tallo Kota Makassar - Achmad Setiawan; Baharuddin Koddeng; Marly Valenti Patandianan (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2013)
Flood is a natural phenomenon that is very complex and difficult to avoid and it happens in almost all regions of Indonesia include in Makassar city. Makassar morphology condition and tilt between 0 – 21 m above sea level and also the existence of three major rivers namely Pampang, Jeneberang and Tallo river. In addition, human activities that alter the function of green open space to settlements due to rapid urban growth become causes of floods. Tallo River was chosen as the venue for research due to the significant influence on the occurrence of flooding in the northern city of Makassar. The vulnerability of the flood is estimated using four parameters including rainfall, soil texture, land cover and slope were scored later and overlayed. Vulnerability level is divided into four classes, which are very vulnerable, susceptible, slightly vulnerable and sensitive. Based on the research, the area that is particularly very vulnerable to flooding in watershed of Tallo about 0.03 km2 , susceptible 56,01 km2 , slightly vulnerable 65.49 km2 , and is not prone area 2.29 km 2 . Vulnerability is then validated usig tidal data to determine areas affected by the flood tide. Causes of flood analysis by using root causes analysis with two parameters of runoff and erosion sub-watershed in order to formulate appropriate concepts for controlling floods which occurred in the city of Makassar.